2002
DOI: 10.1007/s00267-002-2734-3
|View full text |Cite
|
Sign up to set email alerts
|

Legitimizing Fluvial Ecosystems as Users of Water: An Overview

Abstract: We suggest that fluvial ecosystems are legitimate users of water and that there are basic ecological principles guiding the maintenance of long-term ecological vitality. This article articulates some fundamental relationships between physical and ecological processes, presents basic principles for maintaining the vitality of fluvial ecosystems, identifies several major scientific challenges and opportunities for effective implementation of the basic ecological principles, and acts as an introduction to three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
152
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(156 citation statements)
references
References 50 publications
1
152
0
3
Order By: Relevance
“…We considered this related to the drastic hydrological dynamics in the littoral zones of lakes. In fact, for riparian or littoral zones, the hydrological regime often entails large temporal fluctuations in water table elevation (Naiman et al 2002;Nilsson and Svedmark 2002), which significantly influence the process of denitrification and N 2 O emissions (Hefting et al 2003). Therefore, in the littoral zones of Lake Huahu, the complicated temporal variation of N 2 O emissions should be partly explained by temporal variation of standing water depths (Table 1) The estimation of N 2 O emissions is very difficult due to technical difficulties in measurements and the large spatiotemporal variation in N 2 O production, consumption, and transport rates (Hefting et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…We considered this related to the drastic hydrological dynamics in the littoral zones of lakes. In fact, for riparian or littoral zones, the hydrological regime often entails large temporal fluctuations in water table elevation (Naiman et al 2002;Nilsson and Svedmark 2002), which significantly influence the process of denitrification and N 2 O emissions (Hefting et al 2003). Therefore, in the littoral zones of Lake Huahu, the complicated temporal variation of N 2 O emissions should be partly explained by temporal variation of standing water depths (Table 1) The estimation of N 2 O emissions is very difficult due to technical difficulties in measurements and the large spatiotemporal variation in N 2 O production, consumption, and transport rates (Hefting et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that N 2 O emissions were significantly correlated with the fourth component, influenced by water temperatures and soil water content (Table 2). In fact, for riparian or littoral marshes, the hydrological regime often entails large temporal fluctuations in water table elevation (Naiman et al 2002;Nilsson and Svedmark 2002), which significantly influence the process of denitrification and N 2 O emissions (Hefting et al 2003). Therefore, in such littoral marshes of the TGR, the complicated temporal variations of N 2 O emissions should be partly explained by the temporal variation of the standing water table and thermal conditions in the growing season.…”
Section: Key Factors Influencing N 2 O Emissions From Littoral Marshementioning
confidence: 99%
“…Temporal and spatial variability in river flow is recognised as a fundamental control on instream habitat structure and availability, and riverine ecosystem biodiversity and integrity (Naiman et al, 2002;Richter et al, 2003;Arthington et al, 2006;Dudgeon et al, 2006). Instream faunal communities are adapted to the 'natural' flow regime and the variability in magnitude, frequency, timing and duration of high, low and intermediate flow events (e.g., Jowett and Duncan, 1990;Lytle and Poff, 2004;Monk et al, 2006).…”
Section: Introductionmentioning
confidence: 99%